Tra Scilla e Cariddi: diventare adulti in un reparto di medicina - Eugenio Zito (EtnoAntropologia)
In the article I present some anthropological reflections, with reference to ethnographic material collected on the field, the pediatric ward for the treatment of type 1 diabetes in a Neapolitan university hospital, about the transition rite of diabetic patients who had reached legal age from pediatric services to clinical units for adults. In particular the paper focuses, through the story of Khalid, a young diabetic immigrant of Moroccan origin, on the medical practice of joint outpatient clinic, drawn up to facilitate this complex passage and on the usefulness of a narrative approach to chronic disease in health settings.